Potential Anti-Obesity Effect of Hazel Leaf Extract in Mice and Network Pharmacology of Selected Polyphenols - Jiarui Zhao; Aikebaier Alimu; Yvmo Li; Zhi Lin; Jun Li; Xinhe Wang; Yuchen Wang; Guangfu Lv; He Lin; Zhe Lin (MDPI AG, 2024)
Background: Obesity is gradually becoming a widespread health problem, and treatment using natural compounds has seen an increasing trend. As a by-product of hazelnut, hazel leaf is usually disposed of as waste, but it is widely used in traditional and folk medicines around the world. Aim of this study: Based on previous studies, the effects of the regulation of lipid metabolism and the mechanism of hazel leaf polyphenol extraction obesity were investigated. Methods: In this study, a high-fat diet-fed mouse model of obesity and 3T3-L1 preadipocytes were established. The ameliorative effects of the hazel leaf polyphenol extract on obesity and the regulating lipid metabolisms were explored based on network pharmacology, gut microbiota, and molecular docking. Results: Network pharmacology showed that hazel leaf polyphenols may play a role by targeting key targets, including PPARγ, and regulating the PPAR signaling pathway. They significantly improved body weight gain, the liver index, and adiposity and lipid levels; regulated the gut microbiota and short-chain fatty acid contents; down-regulated the expression of lipid synthesis proteins SREBP1c, PPARγ, and C/EBP-α; and up-regulated the expression of p-AMPK in obese mice. They inhibited the differentiation of 3T3-L1 cells, and the expression of related proteins is consistent with the results in vivo. The molecular docking results indicated that gallic acid, quercetin-3-O-beta-D-glucopyranoside, quercetin, myricetin, and luteolin-7-O-glucoside in the hazel leaf polyphenol extract had strong binding activities with PPARγ, C/EBP-α, and AMPK. Conclusions: The results demonstrate that the hazel leaf polyphenol extract can improve obesity by regulating lipid metabolism, which provides a valuable basis for developing health products made from hazel leaf polyphenols in the future.